HERBAL MEDICINES AND THEIR USE - Bilaliddin Aloviddinov; Yusupova Zebo Khusnutdinovna (Лучшие интеллектуальные исследования, 2024)
The article discusses the pharmacological properties of medicinal products containing combinations of medicinal plant extracts as active ingredients: thyme, ivy and primrose. The article discusses the causes and mechanisms of cough, as well as the possibilities of its treatment with the help of herbal preparations, since herbal medicine occupies a special niche in the treatment of acute respiratory infections. Biologically active substances of plants are more naturally included in metabolic processes; treatment with herbal medicinal preparations is characterized by better tolerability and a lower incidence of side effects and complications.